Association between body mass index and dental caries in the Kingdom of Saudi Arabia: Systematic review - Yosef Faraj Amer Alshehri; Joon Soo Park; Estie Kruger; Marc Tennant (Elsevier, 2020)
Objective: The Kingdom of Saudi Arabia (KSA) has one of the highest prevalence of both obesity and dental caries. To date, there has not been any documented evidence linking these two factors. Therefore, the objective was to conduct a systematic review of published studies that have analysed the association between body mass index and dental caries in the KSA for both children and adults. Methods: A systematic database search [PubMed, EMBASE, Web of Science, CINAHL and Cochrane Library] was conducted following the PRISMA guidelines. The inclusion criteria were observational studies, with no limit on the publication date. Search terms included: dental caries, obesity, overweight, body mass index, BMI 'AND' Saudi Arabia. The independent variable was body mass index (BMI), and the primary outcome measure was dental caries prevalence and severity. Results: From 951 search results, 935 citations were identified and excluded. Of the 16 potentially eligible studies, two citations were excluded, because the studies did not meet the inclusion criteria. This left fourteen studies meeting the criteria to be included in this systematic review. Ten studies outlined children, and four studies assessed adults. For children, two studies resulted in a positive association between high BMI and caries, six studies resulted in a negative association, and two studies had a non-significant association. For adults, two studies resulted in a positive association between high BMI and dental caries, and two studies had a non-significant association. These were rated as having low to moderate risk of bias. Conclusion: As a result of this equivocal outcome within the systematic review, body mass index and dental caries present as a complex association. Further long-term studies are required to translate the findings into clinical practice.